Identifikasi Penyebab Anemia pada Ibu Hamil di Puskesmas Sungai Piring - Novita Yanti; Nurlisis Nurlisis; Nur' Afni (Jurnal Kesehatan Komunitas, 2020)
Anemia in pregnancy becomes a particular concern because it is associated with mortality and morbidity in mother and baby, risk of miscarriage, stillbirth, prematurity, and low birth weight. Baby in the womb can experience growth and development disorder, children become less intelligent and stunting. This research aims to analyze the causes of anemia in pregnancy at the Public Health Center of Sungai Piring in 2019. This research is qualitative research, through in-depth interviews, observation, and document search. The research informants were the Head of the public health center, the Head of Administration, the Person in Charge of Maternal and Child Health (KIA), pregnant women, husbands, and parents. The observation was by seeing directly the KIA service, at community health sub-center, Integrated Service Post, Mother class, and P4K home visits and searching for related documents. The result showed that the analysis of anemia causes in pregnancy was lack knowledge of mothers and husbands, lack of husband's support, some officers were still did not informing/providing counseling, lack of human resources (midwives), less attractive/innovative media, geographic, socio-cultural and most of the big mothers did not have health insurance. It is recommended to the public health center to optimizing the budget for activities through National Health Operational Assistance and Health Insurance funds through the proposal in charge of KIA, such as outreach and training activity.